Espaços não-formais de Educação e seus possíveis usos na Educação Infantil: concepções e práticas de professores na Educação em Ciências - Garcia Júnior, Pedro José (2023)
The central objective of the research is to analyze the use/contribution of non-formal education vacancies for Science education among Early Childhood Education teachers at a Municipal Early Childhood Education School in the municipality of Venda Nova do Imigrante – ES. The research is qualitative in nature, exploratory and eminently descriptive, involving 16 Early Childhood Education teachers who work with children aged three to five years old. To produce data during the study, questionnaires and interviews with participating teachers were carried out. For data analysis, data triangulation was chosen, using data from questionnaires and interviews carried out during the research to understand the use and contribution of non-formal educational spaces to Science Education in Early Childhood Education. From this study, we concluded that the participating teachers point to non-formal education spaces as places used to carry out practices involving the experience of Scientific Education with Early Childhood Education Children and that they are relevant to the use of these spaces in the learning process. However, difficulties such as transport, distance and partnerships with the institution (school) were highlighted when carrying out practices in the use of these spaces with children. As an educational product, we used interviews carried out with three teachers to prepare a booklet presenting practices carried out with children using non-formal education spaces in the region.